2018
DOI: 10.1111/zph.12519
|View full text |Cite
|
Sign up to set email alerts
|

Bokeloh bat lyssavirus isolation in a Natterer’s bat, Poland

Abstract: In recent years, Bokeloh bat lyssavirus (BBLV), a member of the novel lyssavirus genus Bokeloh bat lyssavirus in the family Rhabdoviridae, has been detected in Germany (five cases) and France (two cases). Here, we report the isolation of BBLV in a Natterer's bat (Myotis nattereri) in Poland. The bat brain tested positive for rabies using classical diagnostics tests (FAT and RTCIT) and then subsequently confirmed by molecular techniques. Viral RNA was found in all peripheral organs tested, and the highest viral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Daubenton's bat (Myotis daubentonii) is the main reservoir of EBLV-2 [4], and EBLV-2 cases in bats were reported from several European countries [7]. Thus far, lyssaviruses reported from Poland were characterized as EBLV-1 or BBLV [8]. The detection of antibodies against lyssaviruses in two out of three Polish Myotis daubentonii could indicate the presence of EBLV-2 also in Poland, but an interspecies transmission of EBLV-1 from Serotine bats cannot be ruled out either.…”
Section: Discussionmentioning
confidence: 99%
“…Daubenton's bat (Myotis daubentonii) is the main reservoir of EBLV-2 [4], and EBLV-2 cases in bats were reported from several European countries [7]. Thus far, lyssaviruses reported from Poland were characterized as EBLV-1 or BBLV [8]. The detection of antibodies against lyssaviruses in two out of three Polish Myotis daubentonii could indicate the presence of EBLV-2 also in Poland, but an interspecies transmission of EBLV-1 from Serotine bats cannot be ruled out either.…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, Lleida Bat Lyssavirus (LLEBV) was detected also in Miniopterus schreibersii bats in Spain and later on in France [ 105 , 106 ]. Bokeloh bat Lyssavirus (BBLV) was identified in Myotis nattereri in Germany, France, and Poland [ 96 , 99 , 100 ]. Most recently, Kotalahti Bat Lyssavirus (KBLV) was detected in Myotis brandtii in Finland [ 86 , 104 ].…”
Section: European Bat Virusesmentioning
confidence: 99%
“…Within our study, we identified the tenth BBLV case, which is the seventh case in Germany and the fourth case in Lower Saxony isolated from a Natterer’s bat. Since its first detection in 2010 in Germany [ 12 ], BBLV was found several times in Germany, France and Poland [ 16 , 17 ]. The fact that it was again isolated from the same bat species supports the hypothesis of the Natterer’s bat representing the reservoir host species.…”
Section: Discussionmentioning
confidence: 99%
“…BBLV was first discovered in a Natterer’s bat ( Myotis nattereri ) in Lower Saxony in 2010 [ 12 ]. Ever since, it has been isolated several times from this species in Germany, France and Poland [ 16 , 17 ], suggesting that the Natterer’s bat is the reservoir host species.…”
Section: Introductionmentioning
confidence: 99%